Does internal migration improve overall well-being in Ethiopia? - de Brauw, Alan; Mueller, Valerie; Woldehanna, Tassew (Oxford University Press, 2018)
Standard economic models suggest that individuals participate in migration to improve their well-being, whether those decisions are made at the individual or the household level. However, explicit and implicit barriers to movement both within and between countries can hinder migration, potentially affecting welfare improvement. In this article, we use a unique panel dataset of tracked migrants and non-migrants that originate from 18 peasant associations in Ethiopia to examine the welfare impacts of internal migration. Using several techniques, we measure the association of migration with improved welfare among migrants relative non-migrants. We find that migrant welfare improves in a number of different ways; their non-food consumption rises by at least 145%, and we find that migrants also have improved diets relative to non-migrants. Gains are larger among male and urban migrants, as well as migrants who left a longer time in the past. The large welfare contribution of migration, conditional on migrating for employment, suggest that barriers exist, even within countries such as Ethiopia, against the free movement of people to places where they would be objectively better off.